Learning contexts and proficiency matter: L2 real-time sensitivity to conventional and unconventional dative pattern - Hyunwoo Kim; Haerim Hwang (Language and Cognition)
This study investigates L2 learners’ sensitivity to conventional and unconventional dative constructions in English. Experiment 1 focused on measuring EFL learners’ acceptability judgment and real-time processing of sentences containing both types of constructions. Experiment 2, involving ESL learners, aimed to explore the modulating effects of L2 learning contexts and proficiency. Results from Experiment 1 indicated that EFL learners demonstrated diminished sensitivity compared to L1 English speakers, both in acceptability judgment and self-paced reading, with L2 proficiency marginally affecting their performance. In Experiment 2, ESL learners exhibited sentence judgment and processing patterns akin to those of L1 speakers, with L2 proficiency influencing their acceptability judgment and not self-paced reading. These findings support the claim that while L2 learners have a reduced ability to take advantage of statistical preemption, this ability can improve with increased language experience. Crucially, our study extends this theoretical perspective to the domain of real-time sentence processing.